My Reflexivity on Pedagogical Practices of Physics Teachers - Ghimire, Pankaj Sharma (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This paper aims to elaborate my reflection on the instructional practices of physics teachers in theory and experimental classes at technical institutions in the Kathmandu district. I employed an ethnographic research design to conduct the research. I selected two technical institutions in the Kathmandu district to conduct the research, two theory classrooms, and two physics laboratories of those institutions for the participant observation process, and conducted open-ended and unstructured interviews with nine students from those institutions. I observed multiple theory and experimental classes for the entire semester period as a complete observer. In addition, I employed social constructivist learning theory to guide the whole research process. The findings from this study indicated that traditional teacher-centric pedagogical practices were prevalent at those technical institutions.